The Northern Great Barrier Reef a Royal Society discussion held on 28 and 29 January 1976. - Stoddart, D.R.; Yonge, Sir Maurice (London Royal Society, 1978)
Distribution statement from label mounted on t.p."First published in Philosophical transactions of the Royal Society of London: part A in series A, volume 291 ... part B in series B, volume 284."Includes bibliographies and indexes.
Keywords: Great Barrier Reef